Application of the Principle of Truth to Judiciary Institutions: Discourse of Judges at the Makassar Religious High Court, Indonesia - Talli, Abdul Halim; Akram, Andi; Sinelele, Ashar; Dahlan, Dahlan; Hakim, Lukman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The application of the formal truth concept in civil courts, particularly religious courts, ought to have been abandoned. In several civil disputes, judges are guided by the pursuit of formal truth, resulting in unjust verdicts. This study examines the situation of the principle of formal truth in the investigation of civil matters in the Religious Courts and the view of the Makassar Religious High Court Judge regarding its application. This study is a legal-empirical investigation informed by legal philosophy. Techniques for data collecting consisting of in-depth interviews with key informants and research of court decisions and relevant literature. The findings of the study indicate that, first, the principle of formal truth that is applied to religious courts is still legitimate today, just as the HIR/RBg approach of proving civil cases in Indonesian civil courts is still valid. Second, the opinion of the judges of the Makassar Religious High Court regarding the application of the formal truth principle in the environmental courts of the religious courts demonstrates that, in general, the Makassar PTA judges believe that this principle must be applied as a trial process provision. In their opinion, the formal principle of truth serves as a guide for parties and judges when reviewing cases. Several other judges, however, believe that the formal truth principle should be substituted by the material truth.